Tondelli’s Camere separate Through the Lexicon of Roland Barthes - Gagliardi, Laura (Romance eReview, 2017)
This article analyzes Camere separate (Separate Rooms, 1989), the final work of the Italian novelist Pier Vittorio Tondelli (1955-1991), through the theoretical filter of Roland Barthes’ A Lover’s Discourse: Fragments (1977). In his book, Barthes discussed romantic relationships as non-verbal forms of communication: his fragments are possible representations of the specific emotions experienced by partners in a romantic relationship. In his book, Barthes elaborates a lexicon that seeks to translate through images the very language of lovers’ discourses. The author analyzes the structure of Tondelli’s work by deconstructing the plot into key-images, using Barthes’ theoretical lexicon. The ultimate goal is to demonstrate that Tondelli’s novel, neglected when not openly derided by contemporary criticism, could be understood on a level other than the linguistic one. Through the ever-valid theoretical models elaborated by Barthes, it is possible to understand to what extent is Tondelli able to describe the intricacies and complexities of romantic interactions, well beyond the linguistic dimension of literature.